AB0609 Are hydroxychloroquine (HCQ) and leflunomide (LEF) effective in DMARD naive patients with early rheumatoid arthritis (RA)?. (23rd January 2014) - Stoica, S.; Zugravu, G.
Abstract : Background: Both HCQ and LEF are members of disease-modifying antirheumatic drugs (DMARDs)drugs (DMARDs)used to slow down RA progression. They have documented efficacy in reducing signs and symptoms in RA and are widely used as first-line DMARD therapies across Europe. Objectives: To compare early RA patients starting HCQ and LEF, in terms of demographics, baseline characteristics, clinical responses and drug survival. Methods: We investigated 56 DMARD naive RA pacients with disease duration <6 months starting HCQ or LEF. 23 pacients treated with HCQ (400mg/day) and 33 pacients treated with LEF (20 mg/day) met the inclusion criteria. There were significant differences in baseline characteristics between HCQ/LEF pacients: mean age 47.9/53.9 years, DAS28 4.1/5.2, SDAI 22.0/27.2, MHAQ 0.48/0.57, 56%/68% rheumatoid factor positive (p=0.006), 65% vs 74% female (p=0.11). No corticotherapy association was admitted. Baseline characteristics were compared by appropriate statistic tests, drug survival compared by Kaplan-Meier analysis. Pacients were evaluated at baseline, 3 months and 6 months. Results: The results were inferior for HCQ vs LEF (log rank p<0.001), with estimated drug survival rates of 58%/84% and 65%/96% at 3, 6 months. Mean 6-month improvements for HCQ(n=23)/LEF(n=33) were as follows (unadjusted p-values/propensity score quartile-adjusted p-values): DAS28 -1.1/-1.6 (p=0.003/p=0.29), SDAI -6.3/-12.8 (p<0.001/p=0.02), MHAQ -0.12/-0.25 (p=0.002/p=0.03), ESR -5.7/-10.9 (p=0.006/p=0.29), CRP (mg/L) -7.5/-11.9 (p=0.12/p=0.61), physician global -10.8/-18.9 (p<0.001/p=0.004), patient global -7.5/-11.7 (p=0.10/p=0.56). ACR20/50/70 response rates at 3 months and ACR20 at 6 months was in favour of LEF, but no difference for EULAR good responses. ACR20, ACR50 and ACR70 response rates for HCQ/LEF were: 23%/35%, 21%/42%, 15%/24% at 6 months. showed larger improvement for MHAQ, CRP and physician global and higher ACR response rates for LEF vs HCQ. Conclusions: Drug survival was far superior for LEF, and there was a tendency towards superior effectiveness of LEF vs HCQ also when taking the differences in baseline characteristics into account. References: Emery P. Therapeutic approaches for early rheumatoid arthritis. How early? How aggressive? Br J Rheum 1995;34(suppl.2):87-90. van Zeben D, Breedveld FC. Prognostic factors in rheumatoid arthritis. J Rheum 1996;23(suppl.44):31-3. Fries JF. Effectiveness and toxicity considerations in outcome directed therapy in rheumatoid arthritis. J Rheum 1996;23(suppl.44):102-6. Boers M, Tugwell P, Felson DT, et al. World Health Organization and international league of associations for rheumatology core endpoints for symptom modifying antirheumatic drugs in rheumatoid arthritis clinical trials. J Rheum 1994;21(suppl.41):86-9. Porter DR, Capell HA. The "natural" history of active rheumatoid arthritis over 3-6 months - an analysis of patients enrolled into trials of potential disease-modifying anti-rheumatic drugs, and treated with placebo. Brit J Rheum 1993;32:463-6. Disclosure of Interest: None Declared